From Cost to Service: Building a Smarter Fare Model for Buy-the-Service Transit - Asrori, Ahmad Fajar; Handayani, Susanty; Suryobuwono, Abdullah Ade; Subastian, Djamal; Nashrullah, Nashrullah (Dinasti Publisher, 2025)
The transition from traditional cost-based to service-oriented fare models represents a paradigm shift in public transport financing. This study develops a comprehensive fare calculation model for Buy-the-Service (BTS) transit systems that integrates operational costs, user satisfaction, Ability to Pay (ATP), and Willingness to Pay (WTP). Using data from BisKita Trans Bekasi Patriot corridor in Indonesia, we employed multiple linear regression analysis with 314 users to derive a predictive WTP model: WTP = 2,589.329 + (256.865 × Satisfaction) + (0.030 × ATP). Results indicate that operational costs per passenger (IDR 17,060.20) significantly exceed user WTP (IDR 4,178.34), necessitating a subsidy of IDR 12,876.71 per passenger to maintain service sustainability. Statistical validation confirms model robustness (F = 8.377, p < 0.001) with no multicollinearity issues (VIF = 1.097). The study demonstrates that user satisfaction significantly influences fare acceptance, with each satisfaction unit increasing WTP by IDR 256.87. These findings provide actionable insights for policymakers implementing BTS schemes in developing countries, emphasising the critical role of targeted subsidies in balancing affordability with operational viability while maintaining service quality standards.